Dynamics of the surgical microbiota along the cardiothoracic surgery pathway - Romano-Bertrand, Sara; Frapier, Jean-Marc; Calvet, Brigitte; Colson, Pascal; Albat, Bernard; Parer, Sylvie; Jumas-Bilak, Estelle (Frontiers in Microbiology, 2015)
Human skin associated microbiota are increasingly described by culture-independent methods that showed an unexpected diversity with variation correlated with several pathologies. A role of microbiota disequilibrium in infection occurrence is hypothesized, particularly in surgical site infections. We study the diversities of operative site microbiota and its dynamics during surgical pathway of patients undergoing coronary-artery by-pass graft (CABG). Pre-, per- and post-operative samples were collected from 25 patients: skin before the surgery, superficially and deeply during the intervention, and healing tissues. Bacterial diversity was assessed by DNA fingerprint using 16S rRNA gene PCR and Temporal Temperature Gel Electrophoresis (TTGE). The diversity of Operational Taxonomic Units (OTUs) at the surgical site was analyzed according to the stage of surgery. From all patients and samples, we identified 147 different OTUs belonging to the 6 phyla Firmicutes, Actinobacteria, Proteobacteria, Bacteroidetes, Cyanobacteria and Fusobacteria. High variations were observed among patients but common themes can be observed. The Firmicutes dominated quantitatively but were largely encompassed by the Proteobacteria regarding the OTUs diversity. The genera Propionibacterium and Staphylococcus predominated on the preoperative skin, whereas very diverse Proteobacteria appeared selected in peri-operative samples. The resilience in scar skin was partial with depletion in Actinobacteria and Firmicutes and increase of Gram-negative bacteria. Finally, the thoracic operative site presents an unexpected bacterial diversity, which is partially common to skin microbiota but presents particular dynamics. We described a complex bacterial community that gathers pathobiontes and bacteria deemed to be environmental, opportunistic pathogens and non-pathogenic bacteria. These data stress to consider surgical microbiota as a “pathobiome” rather than a reservoir of individual potential pathogens.